Self-efficacy and trust in consumers' use of health-technologies devices for sports. Issue 8 (August 2021) - Chamorro-Koc, Marianella; Peake, Jonathan; Meek, Adam; Manimont, Guljira
Abstract: The commercial market for wearable health technology is growing but the value these technologies provide for consumers is debatable, as many technologies lack formal validation and are being abandoned at a high rate. The enabling of self-efficacy mechanisms in the design of health technologies, through the factors identified by self-determination theory and the Technology Acceptance Model, could increase the uptake and continued use of these devices. The aim of this research was to investigate how and why people use wearable health technology, and to evaluate their experiences from the perspective of perceptions of autonomy, safety, information security, information accuracy and willingness for continued use. Forty-eight sport enthusiasts or athletes, age range 18–65 and over, completed an online survey with 46 questions. A statistical analysis that included a Mann-Whitney U Test and a Person's Correlation analysis indicated that participants who were confident in their use of a health technology showed satisfaction with previous uses and a sense of autonomy leading to an overall positive experience. Issues around data and personal information security were identified, aligning with extant literature. Findings suggest that: (i) past experience play a role in people's perception of self-efficacy, (ii) the tracking of activities enables of autonomy and confidence, (iii) autonomy influences personal willingness to use health technologies, (iv) strong interest in personal health technologies motivates sustained engagement, and that (v) reliability and validity of data impacts on confidence in health technologies. A conceptual model is proposed for consideration when designing and evaluating health technologies, based on the factors supporting self-efficacy and trust in health technologies. Further research is required to develop this model with the aim of informing designers and developers about how to translate these factors into design features for the development of more effective personal health technology. Abstract : Health-tech, Self-efficacy, Sports, Design, Health.